Preclinical validation of anti‐nuclear factor‐kappa B therapy to inhibit human vestibular schwannoma growth. Issue 7 (31st March 2015) - Dilwali, Sonam; Briët, Martijn C.; Kao, Shyan-Yuan; Fujita, Takeshi; Landegger, Lukas D.; Platt, Michael P.; Stankovic, Konstantina M.
Abstract : Vestibular schwannomas (VSs), the most common tumors of the cerebellopontine angle, arise from Schwann cells lining the vestibular nerve. Pharmacotherapies against VS are almost non‐existent. Although the therapeutic inhibition of inflammatory modulators has been established for other neoplasms, it has not been explored in VS. A bioinformatic network analysis of all genes reported to be differentially expressed in human VS revealed a pro‐inflammatory transcription factor nuclear factor‐kappa B (NF‐κB) as a central molecule in VS pathobiology. Assessed at the transcriptional and translational level, canonical NF‐κB complex was aberrantly activated in human VS and derived VS cultures in comparison to control nerves and Schwann cells, respectively. Cultured primary VS cells and VS‐derived human cell line HEI‐193 were treated with specific NF‐κB siRNAs, experimental NF‐κB inhibitor BAY11‐7082 (BAY11) and clinically relevant NF‐κB inhibitor curcumin. Healthy human control Schwann cells from the great auricular nerve were also treated with BAY11 and curcumin to assess toxicity. All three treatments significantly reduced proliferation in primary VS cultures and HEI‐193 cells, with siRNA, 5 μM BAY11 and 50 μM curcumin reducing average proliferation (±standard error of mean) to 62.33% ± 10.59%, 14.3 ± 9.7%, and 23.0 ± 20.9% of control primary VS cells, respectively. These treatments also induced substantial cell death. Curcumin, unlike BAY11, also affected primary Schwann cells. This work highlights NF‐κB as a key modulator in VS cell proliferation and survival and demonstrates therapeutic efficacy of directly targeting NF‐κB in VS. Highlights: Bioinformatic network analysis revealed NF‐κB as a central node in VS pathobiology. Canonical NF‐κB complex is aberrantly active in human VS and derived VS cultures. NF‐κB siRNA & inhibitor BAY 11‐7082 reduce proliferation and survival in VS cultures. Clinically relevant drug curcumin reduces proliferation and survival in VS cultures. Our work demonstrates therapeutic efficacy of directly targeting NF‐κB in VS.